1950
DOI: 10.1182/blood.v5.11.983.983
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism

Abstract: On the basis of experimental and clinical observations and a review of the literature, a concept of the behavior of storage iron in relation to body iron metabolism has been formulated. Storage iron is defined as tissue iron which is available for hemoglobin synthesis when the need arises. This iron is stored intracellularly in protein complex as ferritin and hemosiderin. It would appear that wherever the cell is functionally intact, such iron is available for general body needs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1951
1951
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Across multiple experiments, the lung tissue was the site where T cell responses were most different between the two groups. We speculated that the spleen may offer more available iron (29) than the lung and that functional differences previously observed (Fig. 4E) would be reversible.…”
Section: Iron Deficiency Results In Decreased Anti-viral Functionalit...mentioning
confidence: 88%
“…Across multiple experiments, the lung tissue was the site where T cell responses were most different between the two groups. We speculated that the spleen may offer more available iron (29) than the lung and that functional differences previously observed (Fig. 4E) would be reversible.…”
Section: Iron Deficiency Results In Decreased Anti-viral Functionalit...mentioning
confidence: 88%
“…These observations argue for the assumption of Vaughan (1942) that stored red cells are preferentially broken down by the cells of the reticuloendothelial system rather than by an intravascular mechanism. I n animal experiments Finch et al (1950), who used Fe59-tagged non-viable red cells, showed that such cells are taken up mainly by the spleen. Noyes et al (1959) reported a considerable uptake of non-viable red cells also by the liver in man, but stated that the destruction of the cells appeared to be most rapid in the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is also an important component in enzymes, DNA, and mitochondria. Iron is stored in the form of ferritin and haemosiderin in liver, bone marrow, and spleen [15,20,21]. Adults require about 25 mg of elemental iron for red cell Hb production and cellular metabolism daily.…”
Section: Iron Deficiency (Id) Anaemiamentioning
confidence: 99%